The Making of Cultural Heritage - Heinich, Nathalie (The Nordic Journal of Aesthetics, 2011)
<!–StartFragment–> How does an artefact enter the corpus of national cultural heritage? The answer to this question offers a pragmatic understanding of the reasons why the expansion of national corpuses has been so widespread, generation after generation and especially during the last one. Of course, there are alsomore general “societal” or “cultural” reasons for such a worldwide phenomenon: a number of explanations have already been proposed by philosophers, historians, sociologists, anthropologists. However, one should not underestimate the effects of the inventorial techniques and methods of description used by the specialists of heritage, in that they tend to elevate the level of precision and of specialisation, hence to enlarge the criteria and to increase the number of artefacts worth entering their corpus. A close study of these actual criteria, through a survey conducted according to what is now called “pragmatic sociology” in France, allows us a deeper understanding of what defines cultural heritage, and of the effective values on which it relies: that is, the axiology of cultural heritage. Switching from “why” to “how” <!–EndFragment–>